From 'to cure' to 'to care' in Oncology Toward shared Evidence based practice. (30th September 2020) - Rubba, F; Paparo, E; Capuano, F; Montella, E; Continisio, I G; Iervolino, A; Magri, P; De Angelis, C; De Placido, S; Triassi, M
Abstract: Aims: Oncological disease need a system of care involving hospital staff and informal caregivers. Care-givers are subjected to stressful factors (burden) with repercussions on psycho-physical balance. The project, carried out together with the ONLUS Travel Companions Association and the Multidisciplinary Oncological Groups (GOM) of Brain and Breast Cancers, intends to offer supportive training experiences for care-givers and health workers, offering emotional and practical preparation for the treatments that they will find themselves providing the cancer relative by helping to improve the quality of care and the relationship between the subjects. The professionals participating in the project (doctors, nurses) take part in a training held by professionals from the Association. The care givers, divided into groups, carry out a CBI test (Caregiver Burden Inventory) and training meetings on medical, psychological and social assistance issues. After 3 months from the end of the course, the care-giver carries out the interview with the psychologist and recompiles the CBI. Furthermore, on 30 selected patients of Breast Cancers, GOM, an emotional evaluation questionnaire of their life experience was administered with respect to the stages of the disease pathway. Results: The answers were then analyzed by the word cloud method and summarized in a synthetic map for each question. The most used words to describe the mood during the illness are 'anger, pain, anguish and worry'; while waiting before the visit they are 'long, exhausting, anxious'; towards the doctor 'availability, humanity, kindness, friendliness, professionalism'; with regard to 'excellent, availability' assistance; about social life during the 'unchanged, serene' illness; towards the return home 'joy'. Conclusions: The project is a starting point towards a continuous and progressive humanization of the integrated pathways from 'to cure' to 'to care' in oncology. Key messages: Patients are positively affected from shared initiatives. Word cloud may resume patients moods and thei main issues concerninthe path.